PHENOMENON THE DAY OF THE WEEK EFFECT ON THE INDONESIA, JAPAN, AND AMERICAN STOCK EXCHANGES BEFORE, DURING, AND AFTER THE COVID-19 PANDEMIC - Siti Komariah; Anisya Andriani Ramadhan (Jurnal Ekonomi, 2022)
There is enough information to influence price movement in the capital market. Information this often responded by excessive by investors when take decision investment . This thing usually happen at times certain , especially at the beginning and end day work ( Monday , Friday ). The goal of this research is to determine how the phenomenon of the day of the week effect affects the stock markets of Indonesia (LQ45), Japan (Nikkei), and America (Dow Jones Industrial Average) during the COVID-19 pandemic period of 2019-2021. Also, we want to know if there is a difference in the return of shares on the Indonesia Stock Exchange (LQ45) between Monday and Friday and Tuesday, Wednesday, and Thursday. This is because the very severe covid-19 pandemic had a big effect on stocks and the global economy on Tuesday, Wednesday, and Thursday. We also want to know if there was a difference in the return of stocks in Indonesia, Japan, and the United States during the study period. The data used was index data return share from January 2019 to December 2021, with insufficient time series data for 205 data points. The methods of research used are comparative and event studies. Whereas the technical analysis used is the normality test, paired sample test, and independent sample t-test, Research results showing that there is The Day of The Week Effect at LQ45 Indonesia Stock Exchange is not there is difference In 2019, 2020, and 2021, alternate Tuesday, Wednesday, and Thursday with Monday Friday. Because : p value > 0.05 (95% confidence ). Research results LQ45 testing with Nikkei and LQ45 with DJIA is homogeneous or same , which shows that no there is difference level returns on the LQ45 index and the Nikkei index.